Enhancing Inter-Organizational Collaboration On Public Service Innovation In Central Sulawesi Province - Halim, Rahmawati; Cante, Slamet Riadi; Tahili, Mashuri H.; Munari; Mukarramah (Journal Management & Economics Review (JUMPER), 2025)
Inter-organizational collaboration has been reconceptualized as a strategy to make public service innovation more effective and sustainable. Therefore, this study aims to analyze the relationship between inter-organizational collaboration and public innovation in Central Sulawesi Province in Indonesia. A quantitative method was used, and data were analyzed using descriptive statistics and Structural Equation Modeling (SEM) analysis. The results showed that inter-organizational collaboration, consisting of common aims, power, trust, membership structure, and collaborative leadership, positively contributes to public service innovation. In conclusion, inter-organizational collaboration offers benefits and is feasible for implementation to achieve a more efficient and effective innovation within public organizations.